On a Possible Relationship between Linguistic Expertise and EEG Gamma Band Phase Synchrony - Reiterer, Susanne M.; Pereda, Ernesto; Bhattacharya, Joydeep (Frontiers in Psychology, 2011)
Recent research has shown that extensive training in and exposure to a second language can modify the language organization in the brain by causing both structural and functional changes. However it is not yet known how these changes are manifested by the dynamic brain oscillations and synchronization patterns subserving the language networks. In search for synchronization correlates of proficiency and expertise in second language acquisition, multivariate EEG signals were recorded from 44 high and low proficiency bilinguals during processing of natural language in their first and second languages. Gamma band (30-45 Hz) phase synchronization was calculated mainly by two recently developed methods: coarse-graining of Markov chains (estimating global phase synchrony, measuring the degree of phase synchronization between one electrode and all other electrodes), and phase lag index (estimating bivariate phase synchrony, measuring the degree of phase synchronization between a pair of electrodes). On comparing second versus first language processing, global phase synchronization by coarse-graining Markov chains indicated that processing of the second language (L2) needs significantly higher synchronization strength than first language. On comparing the proficiency groups, bivariate phase synchronization measures (e.g. phase lag index) revealed that during second language processing the low proficiency group showed stronger and broader network patterns than the high proficiency group, with interconnectivities between a left fronto-parietal network. Synchronization cluster analysis also indicated that the network activity was globally stronger in the low proficiency group during second language processing.